A clash-of-civilizations prism in German media? Documenting a shift from political to religious framing of the Israeli–Palestinian conflict. Issue 1 (March 2017) - Lopatin, Esther; Samuel-Azran, Tal; Galily, Yair
The impact of political events on media's conflict coverage prism is widely established. To assess the role of mounting tensions between Muslims and non-Muslims in Europe in 2013–2014 on German media's coverage prism of Muslim-related conflicts, this article compares coverage of the 2008 and 2014 Israeli military operations in Gaza by three major German newspapers. The empirical analysis indicates a dramatic rise in the use of religious terms in 2014, most notably in conservative newspaper Die Welt, and offers evidence of a shift from politics-centered framing of the 2008 Gaza operation to a more religious-centered framing of the 2014 Gaza War. We discuss wider implications of the findings, including their support for the relevance of the clash-of-civilizations theory to contemporary media's conflict coverage modus operandi.